Insights About the Neuroplasticity State on the Effect of Intramuscular Electrical Stimulation in Pain and Disability Associated With Chronic Myofascial Pain Syndrome (MPS): A Double-Blind, Randomized, Sham-Controlled Trial - Botelho, Leonardo; Angoleri, Letícia; Zortea, Maxciel; Deitos, Alicia; Brietzke, Aline; Torres, Iraci L. S.; Fregni, Felipe; Caumo, Wolnei (Frontiers in Human Neuroscience, 2018)
Background: There is limited evidence concerning the effect of intramuscular electrical stimulation (EIMS) on the neural mechanisms of pain and disability associated with chronic Myofascial Pain Syndrome (MPS). Objectives: To provide new insights into the EIMS long-term effect on pain and disability related to chronic MPS (primary outcomes). To assess if the neuroplasticity state at baseline could predict the long-term impact of EIMS on disability due to MPS we examined the relationship between the serum brain-derived-neurotrophic-factor (BDNF) and by motor evoked potential (MEP). Also, we evaluated if the EIMS could improve the descending pain modulatory system (DPMS) and the cortical excitability measured by transcranial magnetic stimulation (TMS) parameters. Methods: We included 24 right-handed female with chronic MPS, 19–65 years old. They were randomically allocated to receive ten sessions of EIMS, 2 Hz at the cervical paraspinal region or a sham intervention (n = 12). Results: A mixed model analysis of variance revealed that EIMS decreased daily pain scores by -73.02% [95% confidence interval (CI) = -95.28 to -52.30] and disability due to pain -43.19 (95%CI, -57.23 to -29.39) at 3 months of follow up. The relative risk for using analgesics was 2.95 (95% CI, 1.36 to 6.30) in the sham group. In the EIMS and sham, the change on the Numerical Pain Scale (NPS0-10) throughout CPM-task was -2.04 (0.79) vs. -0.94 (1.18), respectively, (P = 0.01). EIMS reduced the MEP -28.79 (-53.44 to -4.15), while improved DPMS and intracortical inhibition. The MEP amplitude before treatment [(Beta = -0.61, (-0.58 to -0.26)] and a more significant change from pre- to post-treatment on serum BDNF) (Beta = 0.67; CI95% = 0.07 to 1.26) were predictors to EIMS effect on pain and disability due to pain. Conclusion: These findings suggest that a bottom–up effect induced by the EIMS reduced the analgesic use, improved pain, and disability due to chronic MPS. This effect might be mediated by an enhancing of corticospinal inhibition as seen by an increase in IC and a decrease in MEP amplitude. Likewise, the MEP amplitude before treatment and the changes induced by the EIMS in the serum BDNF predicted it’s long-term clinical impact on pain and disability due MPS. The trial is recorded in ClinicalTrials.gov: NCT02381171.